LEGAL IMPLICATIONS AND NEW CUSTOMS REGULATIONS ON JASA TITIP PRACTICES IN INDONESIA - Leman, Brandon Angelo; Lawritz, Filbert; Laurensia, Jesslyn; Nugraha, Dwi Putra (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The Directorate General of Customs plays a crucial role in regulating the inflow of goods into Indonesia. Digitalization and increasing consumer demand for foreign products have driven the growth of personal shopping services. This activity is often misused through splitting to avoid import duties and taxes. This study aims to analyze the legal implications of the new Customs regulations on personal shopping practices. A normative legal method was applied using a statutory and conceptual approach with primary and secondary legal sources. The discussion shows that splitting is categorized as passive smuggling under Article 102 of Law Number 17 of 2006 on Customs. The government, through Regulation PMK 199/PMK.010/2019, sets import duty exemption limits for personal goods and strengthens oversight mechanisms. Offenders are subject to criminal penalties, fines, and administrative sanctions. The study concludes that Customs regulations do not prohibit personal shopping but aim to ensure compliance and protect state revenue.